2017
DOI: 10.4067/s0717-95022017000300027
|View full text |Cite
|
Sign up to set email alerts
|

Shape, Septa and Scalloping of the Maxillary Sinus

Abstract: RENNIE, C.; HAFFAJEE, M. R. & SATYAPAL, K. S.Shape, septa and scalloping of the maxillary sinus. Int. J. Morphol., 35(3):970-978, 2017. SUMMARY:The maxillary sinus varies according to age, however there are limited studies that have illustrated its 3D form over time. This study aimed to classify the maxillary sinus by the shape, number of septa and scallops in a 1 to 25 year age group, utilising computerized tomography (CT) scans and 3D reconstruction. CT scans (n=480) were reviewed from the picture archiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…On the other hand, some authors have demonstrated that the highest rate of prevalence of maxillary septa occurred in the posterior region ( 8 , 13 , 21 ). Rennie, Haffajee and Satyapal, in turn, noted that the majority of septa were localized in the anterior region of the maxilla ( 22 ). Khalighi Sigaroudi et al .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some authors have demonstrated that the highest rate of prevalence of maxillary septa occurred in the posterior region ( 8 , 13 , 21 ). Rennie, Haffajee and Satyapal, in turn, noted that the majority of septa were localized in the anterior region of the maxilla ( 22 ). Khalighi Sigaroudi et al .…”
Section: Discussionmentioning
confidence: 99%
“…На основі КТ-зображень черепів було оцінено вікові зміни розмірів верхньощелепної пазухи стосовно діаметрів лицевого скелета. Статистичний аналіз (коефіцієнт кореляції та детер-мінації) показав, що розміри та конфігурація верхньощелепних пазух статистично значуще корелюють із параметрами середньої частини обличчя [28][29][30].…”
Section: визначення особливостей контурів дна верхньощелепних пазух у...unclassified
“…The morphological shape of the MS changes with age. When viewed anteriorly, the most common shaped is the rectangle from 1 to 3 years, the triangle from 4 to 12 years, and the upside‐down triangle shape from age 13 onwards (Rennie et al, 2017a). On the lateral view, the MS is quadrilateral across all the age groups with differences only noted along the inferior wall of the sinus which is influenced by teeth eruption.…”
Section: Maxillary Sinusmentioning
confidence: 99%